Precipitation kinetics of gamma double prime phase during direct aging treatment of Inconel 718 superalloy additively manufactured by selective laser melting - Sajad Ghaemifar; Hamed Mirzadeh (Journal of Materials Research and Technology, 2023)
While direct aging of Inconel 718 nickel-based superalloy from the as-built state is known as a promising practice to tune the mechanical properties, the precipitation kinetics of γ″ phase, as the main precipitating phase, has received less attention. Accordingly, in the present work, post-processing in the form of the direct aging treatment of Inconel 718 superalloy manufactured by the laser powder bed fusion additive manufacturing, also known as selective laser melting (SLM), was systematically investigated by microstructural analysis and hardness measurements. It was revealed that the peak aged condition for direct aging can be achieved at much shorter holding times compared to aging after homogenization/solutionizing heat treatment. Moreover, the Johnson–Mehl–Avrami–Kolmogorov (JMAK) analysis based on both hardness measurements and microstructural analysis were applied to unravel the γ″ precipitation kinetics, which respectively led to the precipitation activation energies of 160 and 157 kJ/mol, which are consistent with the activation energy for the diffusion of Nb in IN718 superalloy manufactured by SLM. Moreover, the Lifshitz–Slyozov–Wagner (LSW) diffusion-controlled growth theory was modified to become applicable for investigating the precipitation kinetics during the evolution of the volume fraction of the precipitating phase, which also led to the activation energy of 157 kJ/mol. These results can also shed light on the procedures used for investigating the kinetics of phase transformations during aging of additively manufactured Inconel 718 superalloy.